Progressive Islamic Education in the Digital Age: Application of Game Application Media as an innovation in Islamic Education learning - Haya Ula Nadifa; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2025)
The era of globalization and rapid technological advancements has transformed the education sector by offering new opportunities and challenges. Technology-based learning requires educators to continuously enhance their digital competencies to ensure effectiveness in the learning process. This study employs a literature review method to examine the application of game-based media as an innovation in Islamic Religious Education (PAI). Data were collected from reputable academic sources such as Google Scholar, ScienceDirect, and other scientific databases. The findings indicate that the integration of educational games in PAI learning significantly improves students’ learning motivation, strengthens their understanding of religious concepts, and fosters critical thinking skills through interactive and engaging activities. Moreover, game-based learning contributes positively to character development by reinforcing moral and spiritual values within the learning process. Therefore, digital educational games serve as a promising learning innovation that supports the improvement of Islamic Education quality in the digital era.